Nurses’ Perceptions and Expectations of Patient Violence: Language Matters - Darcy Copeland; Mary Potter; Susan Tipton; Debra Culter (Nursing Reports)
Background: Patient violence is a serious occupational risk for nurses. Some professional rhetoric presents this risk as not part of nursing work, discounting widespread exposure. There is a disjunction between nurses’ experiences and the discourse they are exposed to. There is little to no evidence indicating whether nurses think it is possible to eliminate patient violence or whether their expectations of exposure to patient violence align with the significant risk they face. Purpose: The purpose of this analysis was to examine nurses’ perceptions related to the elimination of, expectations of, and desired state regarding exposure to patient violence. Methods: This study used a cross-sectional, descriptive design. Results: Nearly 500 nurses from seven acute care hospitals in the western United States responded to the electronic survey. Most nurses (85%) do not think it is possible to prevent violence in acute care facilities. Most (81%) also agree that nurses in acute care facilities do expect to be exposed to patient violence while at work. A smaller majority (68%) responded that nurses should expect to be exposed to patient violence while at work. Respondents indicated that expecting patient violence was an important mechanism in preventing and responding to it. Nurses did not conflate expectations of patient violence with acceptance of patient violence. Conclusions: Expecting patient violence is not equivalent to accepting violence, yet these two ideas are often used interchangeably in workplace violence initiatives. Eliminating patient violence is not entirely possible given known risk factors. Enforcing ‘zero tolerance’ to patient violence is untenable, and the inability to enact it may result in frustration among nurses. Language matters, and what nurses are experiencing must be differentiated from an ideal state. The professional narrative about patient violence may have negative consequences and is not aligned with nurses’ experiences or expectations.